2002
DOI: 10.1080/000163502753509545
|View full text |Cite
|
Sign up to set email alerts
|

Caries reduction in Belgian 12-year-old children related to socioeconomic status

Abstract: This study compares dental caries reduction in Belgian 12-year-old children of different socioeconomic status in 1983 and 1998. Moreover, the relative effect of dental health factors on caries reduction is estimated. In the region of Brussels, children in the 7th grade at the same schools participated in cohort 1983 (n = 533) and in cohort 1998 (n = 496). DMFT, DMFS, and dental fluorosis were clinically recorded. The socioeconomic status of the children was established on the basis of their parents' education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
3
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 14 publications
3
15
3
6
Order By: Relevance
“…Despite the low caries level reported in Tanzania, many studies have warned of the possible rise of dental caries prevalence as far as economic situation allows a changed life style favoring consumption of sugary food stuffs (7,8) Furthermore, the provision of preventive oral health services in the country is still poor. In other countries where oral health preventive services have been improved, a significant decrease in dental caries has been observed (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the low caries level reported in Tanzania, many studies have warned of the possible rise of dental caries prevalence as far as economic situation allows a changed life style favoring consumption of sugary food stuffs (7,8) Furthermore, the provision of preventive oral health services in the country is still poor. In other countries where oral health preventive services have been improved, a significant decrease in dental caries has been observed (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Dabei polarisiert sich die Karieshäufigkeit zunehmend, d. h. eine immer kleinere Gruppe vereinigt den größten Teil der erkrankten Zähne auf sich. Ergebnisse von Untersuchungen zur Mundgesundheit weisen den sozioökonomischen Status als eine wesentliche Determinante aus [3,4,5,6]. Oralepidemiologische Studien sprechen auch von einer zunehmenden sozialen Schieflage des Kariesbefalls [7].…”
Section: Hintergrund Und Fragestellungunclassified
“…The tooth types with the highest caries experience are first molars followed by second molars. Concerning the groups of teeth, molars are often and premolars are seldom attacked by dental caries [Carvalho et al, 2001;Van Nieuwenhuysen et al, 2002;Batchelor and Sheiham, 2004;Carvalho, 2014]. A recent Danish study has shown that half of the caries experience in 18-year-olds is located occlusally, although the occlusal surfaces constitute less than 15% of all surfaces in the dentition [Nørrisgaard et al, 2016].…”
mentioning
confidence: 99%